Protective effects of triple fermented barley extract (FBe) on indomethacin-induced gastric mucosal damage in rats - Jong-Min Lim; Chang-Hyun Song; Su-Jin Park; Dong-Chan Park; Go-Woon Jung; Hyung-Rae Cho; Khawaja Muhammad Imran Bashir; Sae Kwang Ku; Jae-Suk Choi (BMC, 2019)
Abstract Background Hordeum vulgare L (barley) contains numerous phenolic substances with proven anticancer, antioxidant and gastroprotective activities. Saccharification increases the functionality and bioavailability of these compounds thus can aid in the development of a natural product based medicine. This study aimed to investigate the possible gastroprotective effects of saccharification on the indomethacin (IND)-induced gastric ulcers in rats using Weissella cibaria- and Saccharomyces cerevisiae-triple fermented H. vulgare extract (FBe). Methods In total, 60 healthy male 6-week old Sprague-Dawley SD (SPF/VAF Outbred CrljOri:CD1) rats were commercially purchased. The FBe extract (100, 200, and 300 mg kg− 1) was orally administered 30 min before an oral treatment of IND (25 mg kg− 1). Six hours after IND treatment, variations in the histopathology, myeloperoxidase (MPO) activity, gross lesion scores, lipid peroxidation, and antioxidant defense system component (superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH)) levels were measured. Results FBe treatment showed significant (p < 0.01 or p < 0.05) and dose-dependent decrease in gastric mucosal damage. In the present study hemorrhagic gross lesions, gastric MPO activity, and histopathological gastric ulcerative lesions were observed in IND-treated rats compared to the IND control rats. In particular, FBe, in a dose-dependent manner, strengthened the antioxidant defense systems, decreased lipid peroxidation and CAT activity by increasing the GSH levels and SOD activity, respectively. The 200 mg kg− 1 dose of FBe was similarly gastroprotective as the 10 mg kg− 1 dose of omeprazole in rats with IND-induced gastric mucosal damage. Conclusions The findings of the present study show that an oral administration of FBe had positive gastroprotective effects through strengthening the body antioxidant defense system and anti-inflammatory effects.